Leadership presence (Harvard Business Review Press, 2018)
Deconstructing executive presence: what is this ephemeral but critical quality? How new managers can send the right leadership signals: understand the impact you have on others; To sound like a leader, think about what you say, and how and when you say it: think strategically about your communication; Connect, then lead: avoid ruling through fear.